Integrated biological-chemical control of Botrytis gray mould of chickpea - S. JAYANTHI, H.S. TRIPATHI2; Y.P.S. RATHI2, M.P. HAWARE, P.K. MUKHERJEE1, I.M. LENNE (Indian Phytopathology, 2002)
During 1994-96, Trichoderma viride and vinclozolin were used for the integrated control of B. cinerea on chickpeas in Pantnagar, Uttar Pradesh, India.